2020
DOI: 10.1155/2020/2580259
|View full text |Cite
|
Sign up to set email alerts
|

Ethnobotanical Description and Biological Activities of Senna alata

Abstract: Senna alata is a medicinal herb of Leguminosae family. It is distributed in the tropical and humid regions. e plant is traditionally used in the treatment of typhoid, diabetes, malaria, asthma, ringworms, tinea infections, scabies, blotch, herpes, and eczema. e review is aimed at unveiling the ethnobotanical description and pharmacological activities of S. alata. Different parts of the plant are reported in folk medicine as therapeutic substances for remediation of diverse diseases and infections. e extracts a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 71 publications
0
39
0
2
Order By: Relevance
“…Medicinal herbs are regarded as the fundamental and safest therapeutic approach since primordial time and have significantly played lifesaving roles in primary health care development [1,2,3]. According to World Health Organisation, herbal medicine is appraised as alternative therapeutic system to achieve total health care against various diseases such as gonorrhoea, syphilis, typhoid, malaria, cholera, measles, and ulcer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal herbs are regarded as the fundamental and safest therapeutic approach since primordial time and have significantly played lifesaving roles in primary health care development [1,2,3]. According to World Health Organisation, herbal medicine is appraised as alternative therapeutic system to achieve total health care against various diseases such as gonorrhoea, syphilis, typhoid, malaria, cholera, measles, and ulcer [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many species of Senna are commonly used in foods and herbal medicine [85]. In different parts of the world, the whole Senna alata plant is currently being used in the treatment of flu, fever, malaria, and large number of other medical conditions due to the presence of bioactive compounds in the plant, including quinones, alkaloids, and terpenes [86][87][88][89][90]. The leaf extract of Senna alata considerably inhibited 3D7 strain of the Plasmodium falciparum parasite in vitro [87,88].…”
Section: Herbal Therapies Against Covid-19mentioning
confidence: 99%
“…Fernandez et al (2017) showed that Tetradenia riparia was more active on the Gram positive bacteria strains [26]. Cassia alata also showed potential antibacterial effect [36]. Although certain crude extracts from studied botanicals have been shown to be inactive, fractionation studies are needed to determine the active fractions.…”
Section: Antibacterial Activitymentioning
confidence: 99%